The Investment Security of Ukraine: Status and Prospects of Improvement - Sytnyk Natalia S.; Repeta Mariia M. (Bìznes Inform, 2018)
The article is aimed at studying the current status of investment security of Ukraine and determining prospective ways to improve its investment attractiveness. The role of investment security of the State in the economic development is substantiated and its main goals at both the national and the international levels are identified. The components of the investment security system and principles of its functioning in the conditions of modern development of economic processes are considered. Ukraine’s positions in the global rankings, characterizing the investment climate and the business environment of the State, are researched. The authors systematize information on the volume of foreign direct investments in the Ukrainian economy, the main countries-investors of these capital investments, as well as on the main sectors of the national economy the investment resources were directed to. On the basis of macroeconomic calculations, the most important indicators of investment security in 2017 are analyzed. Practical recommendations for increasing the volume of investment capital in the national economy and improving the level of its Investment security. are proposed. Prospects for further research in this direction are development of the strategic investment policy to ensure the reliability of investment security, taking attention of all factors to influence its current status.